Persebaran Fenomena Suhu Tinggi melalui Kerapatan Vegetasi dan Pertumbuhan Bangunan serta Distribusi Suhu Permukaan - Eggy Arya Giofandi (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2020)
Urban heat island is one of the events where the temperature in the metropolitan area is warmer than the surrounding area. Indonesia is located in a tropical climate making several cities potentially increase in temperature during the dry season. As a representative, the City of Pekanbaru is one of the cities with infrastructure growth that is fast including on the island of Sumatra. Population growth and high enthusiastic of residents to find work in the city made land on the edge of the city built up. This makes the green space less and less with the uneven distribution of green space in the city of Pekanbaru. The number of buildings that exist makes the temperature rise in urban areas with an initial temperature of 29oC to 36oC. temperature increases occurred throughout the year with the hottest peaks of temperatures reaching 37oC on April 15, 2013. Whereas in 2009 there was a decrease in temperature with levels ranging from 27oC. This makes the city of Pekanbaru one of the hottest cities in Indonesia. This study uses Landsat 5 imagery for 2000 and 2009, and Landsat 8 for 2018 with the Land Surface Temperature (LST) method and Normalized Difference Built-up Index (NDBI) which are useful to explain the urban heat island distribution (UHI) in Pekanbaru City